Plasminogen Binding Properties of Macrophage Inflammatory Protein (MIP)-2α - Arza, Begoña; Félez, Jordi; Fábregas, Pere; Laroche, Yves; Collen, Désiré; Lijnen, Roger H. (Thrombosis and Haemostasis, 2000)
The chemokine macrophage inflammatory protein (MIP)-2α was identified as a plasminogen binding protein by phage display analysis. MIP-2α and a truncated form lacking 5 lysine residues in the COOHterminal region (mut-MIP-2α) were expressed in E. coli and purified to apparent homogeneity. Purified MIP-2α but not mut-MIP-2α bound specifically to plasminogen, with KA of 3.7×105 M−1 for the interaction of plasminogen with surface-bound MIP-2α. Binding and competition experiments indicated that the interaction involves the region comprising the first 3 kringles of plasminogen and the COOH-terminal lysine-rich domain of MIP-2α. Activation of plasminogen bound to surface-associated MIP-2α by two-chain urokinase-type plasminogen activator (tcu-PA) was about 2.5-fold more efficient than in solution (catalytic efficiency kcat/KM of 0.1 µM−1s−1, as compared to 0.04 µM−1s−1). In contrast, binding of plasminogen to MIP-2α in solution was very weak, as evidenced by the absence of competition of MIP-2α with lysine-Sepharose or with human THP-1 cells for binding of plasminogen. In agreement with this finding, addition of excess MIP-2α did not affect the main functional properties of plasmin(ogen) in solution, as indicated by unaltered activation rates of plasminogen by tcu-PA or tissuetype plasminogen activator (t-PA), t-PA-mediated fibrinolysis, and inhibition rate of plasmin by α2-antiplasmin. Thus, association of MIP-2α with surfaces exposes its COOH-terminal plasminogen-binding site, and may result in enhanced local plasmin generation.
Keywords: MIP-2α; plasminogen; phage display